2011
DOI: 10.1029/2011wr010612
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on front morphology for two‐phase flow in heterogeneous porous media

Abstract: [1] In this work, we studied the influence of heterogeneities, fluid properties, and infiltration rates on front morphology during two-phase flow. In our experiments, a sand box, 40 cm  60 cm  1.2 cm, was packed with two different structures (either random or periodic) composed of 25% coarse material and 75% fine material. The infiltration process was characterized by the capillary number, Ca, and the viscosity ratio, M, between the fluids. The displacing and the displaced fluid had the same densities, such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…NAPL displacement of water observed in a water-wet micromodel was unstable and resulted in multipore blobs of residual water, whereas in an oilwet micromodel displacement was smooth with occasional single-pore blobs of residual water [Grate et al, 2013]. Heiß et al [2011] examined NAPL displacement of water with no buoyancy (q NAPL 5q water ) in waterwet heterogeneous sediments and observed that residual water became entrapped as isolated macroscopic clusters and that the amount of entrapment depended on the heterogeneity structure and the NAPL infiltration rate. In water-wet fractured limestone blocks, residual DNAPL saturation decreased with increased dip of the fracture and trapped blob length depended on fracture roughness and aperture width distribution [Longino and Kueper, 1999].…”
Section: Experimental Studies Of Napl Flow and Entrapmentmentioning
confidence: 95%
See 1 more Smart Citation
“…NAPL displacement of water observed in a water-wet micromodel was unstable and resulted in multipore blobs of residual water, whereas in an oilwet micromodel displacement was smooth with occasional single-pore blobs of residual water [Grate et al, 2013]. Heiß et al [2011] examined NAPL displacement of water with no buoyancy (q NAPL 5q water ) in waterwet heterogeneous sediments and observed that residual water became entrapped as isolated macroscopic clusters and that the amount of entrapment depended on the heterogeneity structure and the NAPL infiltration rate. In water-wet fractured limestone blocks, residual DNAPL saturation decreased with increased dip of the fracture and trapped blob length depended on fracture roughness and aperture width distribution [Longino and Kueper, 1999].…”
Section: Experimental Studies Of Napl Flow and Entrapmentmentioning
confidence: 95%
“…Heiß et al . [] examined NAPL displacement of water with no buoyancy ( ρNAPL=ρwater) in water‐wet heterogeneous sediments and observed that residual water became entrapped as isolated macroscopic clusters and that the amount of entrapment depended on the heterogeneity structure and the NAPL infiltration rate. In water‐wet fractured limestone blocks, residual DNAPL saturation decreased with increased dip of the fracture and trapped blob length depended on fracture roughness and aperture width distribution [ Longino and Kueper , ].…”
Section: The Organic Napl Sourcementioning
confidence: 99%
“…Literature observations about laboratory experiments report that even apparently homogeneous samples give flow patterns which are not consistent with standard models [20], [21]. In this sense, small scale heterogeneities cause the flow to develop channels and fingers Fig.…”
Section: Introductionmentioning
confidence: 92%
“…Experimental characterization of crude oil contaminant entrapment and movement within unsaturated pores has shown that the dispersion process can cause the development of fingers due to pore-scale heterogeneity and fluid interactions (Ovdat and Berkowitz, 2006). Furthermore, residual waters are typically trapped as isolated macroscopic clusters as a result of crude oil displacement of water without buoyancy in water-wet heterogeneous sediments, with the degree of entrapment depending on the heterogeneity structure and crude oil penetration rate (Heib et al, 2011).…”
Section: Experimental Approachmentioning
confidence: 99%